Migrant Identity in Partir Written by Tahar Ben Jelloun - Astri Adriani Allien (Culturalistics: Journal of Cultural, Literary, and Linguistic Studies, 2018)
Partir, a novel by a francophone writer, Tahar Ben Jelloun tells about a Marocco man, Azel, who has a strong willingness to go out of his country. One of the countries he visited is Spain. Compared to other countries, Spain is the closest to Tangier, the city where Azel comes from. This paper aims to analyze the identity of immigrants as represented by Azel, the main character of Partir, by using  a postcolonial approach. Azel’s relationship with Miguel, as the representation of the West, shows that there is a sharp distinction concerning the view that the West is the superordinate, and the East, as the subordinate. Even though the colonialism period has been over, the domination of the West over the East has been still going on under different levels of periods.        Key words: immigrant, identity, colonialism, superiority.